Perceptions of Traditional Voice Calls and Over-the-Top (OTT) Communication Services among Thai Consumers - Amnist Opapun; Chate Khemakongkanonth; Pratompong Srinuan (International Telecommunications Society (ITS), 2024)
We analyzed unique panel data from NBTC to uncover Thai consumers' preference toward Over-the-top (OTT) communication service and traditional voice call in the post-Covid-19 period. Employing a dynamic panel model, we estimate the demand relationship between telecommunication services. We found that Thai consumers perceive traditional voice call and OTT communication as separate services. Moreover, they remained unchanged from pre-pandemic time. Traditional voice call service is likely used to return incoming traditional voice call. This helps the regulators in defining market around OTT communication service and traditional voice call service.
Keywords: 330; OTT communications; Substitution; Traditional voice calls; Dynamic panel model; Thailand